PENERAPAN MEDIA PEMBELAJARAN BERBASIS KOMIK DALAM MENINGKATKAN LITERASI MEMBACA MELALUI MODEL SQ3R PADA MATA PELAJARAN BAHASA INDONESIA SEKOLAH DASAR - Rahmawati, Riska; Eri Purwanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of comic-based learning media in improving students’ reading literacy through the SQ3R model, which is based on the low level of students’ reading interest in Indonesian language subjects caused by the lack of attractive learning media and appropriate teaching methods. This research employed a qualitative method with thirty-seven students as the research subjects. Data collection techniques included reading literacy tests using comics, observation, interviews, and documentation. The results of the study show that the implementation of comic-based learning media combined with the SQ3R method can significantly improve students reading literacy compared to conventional learning. This study concludes that comic based learning media through the SQ3R model is effective in improving students reading literacy in Indonesian language learning at elementary schools.